1994
DOI: 10.1210/jcem.79.1.8027260
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-dependent secretion of macrophage colony-stimulating factor by human endometrial stromal cells of nonpregnant uterus in culture.

Abstract: Recent studies have suggested that macrophages colony-stimulating factor (M-CSF), a hematopoietic glycoprotein essential to the proliferation and differentiation of mononuclear phagocytes and their progenitor cells, is also involved in the reproductive process in mice and humans. In this study, we examined, by enzyme-linked immunosorbent assay, the supernatants of stromal cell-enriched fraction (SF) of human nonpregnant endometrium for the presence of M-CSF during culture with progesterone (P) or estrogen. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It has become apparent that endometrial cells themselves can produce some cytokines.Kauma et alreported that the human endometrium and decidua expressed M-CSF mRNA,and the M-CSF protein was found in extracts from the endometrium [27].By means of ELISA with specific anti-M-CSF antibodies,we have reported that human endometrial stromal cells produce M-CSF and the production was dependent on progesterone but not on estrogen added to the cultures [28].In the present study,with Northern blot analysis,we confirmed a 4-kb mRNA for M-CSF in human endometrial stromal cells,and revealed that M-CSF mRNA expression was increased with progesterone supplementation (Fig.4).In these culture experiments,the level of mRNA expression in the cells was dependent on the amount of progesterone added to the cultures (Fig.5).…”
Section: Cytokine Mrna Expression In the Endometriummentioning
confidence: 68%
“…It has become apparent that endometrial cells themselves can produce some cytokines.Kauma et alreported that the human endometrium and decidua expressed M-CSF mRNA,and the M-CSF protein was found in extracts from the endometrium [27].By means of ELISA with specific anti-M-CSF antibodies,we have reported that human endometrial stromal cells produce M-CSF and the production was dependent on progesterone but not on estrogen added to the cultures [28].In the present study,with Northern blot analysis,we confirmed a 4-kb mRNA for M-CSF in human endometrial stromal cells,and revealed that M-CSF mRNA expression was increased with progesterone supplementation (Fig.4).In these culture experiments,the level of mRNA expression in the cells was dependent on the amount of progesterone added to the cultures (Fig.5).…”
Section: Cytokine Mrna Expression In the Endometriummentioning
confidence: 68%
“…In human nonpregnant endometrial tissues, the tissue-extractable level of immunoreactive M-CSF in secretory endometrial tissue is higher than that in proliferative endometrial tissue [15]. Furthermore, progesterone has a dose-dependent effect on M-CSF production by the stromal cell-enriched fraction of the human non-pregnant endometrium in vitro [13]. M-CSF has several isoforms, and bovine M-CSF is expressed mainly as 3-and 4-kb transcripts; the 3-kb mRNA encodes the membrane-bound form, and the 4-kb mRNA encodes the secreted form.…”
Section: Discussionmentioning
confidence: 91%
“…A number of researchers have reported that M-CSF and its receptor are expressed in the female reproductive tract and that M-CSF plays an important role in pregnancy in mice [1,2,[21][22][23], humans [8,[11][12][13], pigs [35] and cows [3,17,19]. Furthermore, M-CSF concentrations in maternal peripheral blood during the estrous cycle and pregnancy have been reported in humans and mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effects of danazol on ESC activation into G-CSF-secreting cells are opposite to the effects of M-CSF, which induces ESC activation into G-CSF-secreting cells. M-CSF is produced in the human endometrium, particularly by decidual cells (33,34). IL-8 secretion by ESCs is regulated by endometrial IL-1 and IL-1 receptor antagonist (31).…”
Section: Discussionmentioning
confidence: 99%